ANALISIS DATA SURVEY PRESSURE-TEMPERATURE-SPINNER (PTS) SUMUR PANAS BUMI SATU FASA UAP YANG TERIDENTIFIKASI CROSSFLOW - Firmannanda, Ganar
Pressure-Temperature-Spinner (PTS) survey is performed in single-phase vapor geothermal well. In previous analysis, crossflow is identified which is expected because of barrier in the reservoir. PTS data analysis is performed to obtain well quantitative data such as feedzones locations, mass flow, and fluid enthalpy. Processed data is response of spinner to cable speed which is converted into fluid flow rate. Wellbore Simulator used to validate and quantifying the data, where this simulator uses the energy balance and the conservation of momentum to predict pressure lost and enthalpy change along a segment of depth with a specific rate and fluid properties. Massflow contribution, enthalpy of the zones and the major feedzone is known by that process. Reservoir pressure and PI can be estimated by the processed data. So that the difference of reservoir pressure profile along the productive zone which indicated the barrier in the reservoir is known from the calculations of reservoir pressure correction.